Ten Steps for NPH Management: Advancements in Diagnosis and Treatment of Adult Hydrocephalus - Roman, Alex; Takkar, Prince; Maiti, Tanmoy (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2023)
Objectives The authors of the present study intend to describe a straightforward protocol for normal pressure hydrocephalus diagnosis and management, with the employment of a multidisciplinary team approach effort.Methods Using a strict methodological approach for initial diagnosis, taking into consideration occupational therapy and physical therapy assessment, the authors have set out to elaborate a simple protocol for suspicion and, once diagnosed, treatment of normal pressure hydrocephalus. We have used the MoCA (Montreal Cognitive Assessment) and walking assessment that included speed, independence, and distance (SID), 10 m walk test, TUG (timed up and go) evaluation, 6-minute Walk Test, MiniBESTest, as the main factors for pre and post lumbar drainage assessment, after which, the alternatives were deliberated and followed, or not, by ventriculoperitoneal shunt insertion.Results The authors have described a protocol, consisting of ten easy steps, which involves a multidisciplinary team, including occupational therapy and physical therapy professionals, as well as neurologists and neurosurgeons for improved and objective assessment prior to insertion of lumbar drain and, thereafter, detecting the population at most benefit for ventriculoperitoneal shunt insertion. We have described the Ten Step Approach for Normal Pressure Hydrocephalus management, including from initial clinical presentation and imaging, to pre and post lumbar drainage, for lastly deciding upon necessity for ventriculoperitoneal shunt insertion.Conclusions A straightforward protocol for normal pressure hydrocephalus seems not only feasible, but simple to implement in most neurosurgical departments, with good accuracy of prediction of lumbar drainage assessment to shunting outcomes.
Keywords: normal pressure hydrocephalus; ventriculoperitoneal shunt; idiopathic normal pressure hydrocephalus; adult hydrocephalus